2020
DOI: 10.1108/hff-01-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the chamber inclination angle and heat-generating element location on thermal convection of power-law medium in a chamber

Abstract: Purpose This paper aims to study the mathematical modeling of passive cooling systems for electronic devices. Improving heat transfer is facilitated by the correct choice of the working fluid and the geometric configuration of the engineering cavity; therefore, this work is devoted to the analysis of the influence of the position of the heat-generating element and the tilted angle of the electronic cabinet on the thermal convection of a non-Newtonian fluid. Design/methodology/approach The area of interest is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In addition, the difference between the experimental results and those obtained by numerical simulation is less than 5%. Loenko et al 15 investigated numerically the position effect of a heat-generated local element, simulating an electronic device, inside a closed cavity filled with a non-Newtonian fluid for different inclination angles of the cavity. Their results indicated that minimum average heat generating element temperature is obtained when the cavity is not inclined and for the case with a pseudo-plastic working fluid (n < 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the difference between the experimental results and those obtained by numerical simulation is less than 5%. Loenko et al 15 investigated numerically the position effect of a heat-generated local element, simulating an electronic device, inside a closed cavity filled with a non-Newtonian fluid for different inclination angles of the cavity. Their results indicated that minimum average heat generating element temperature is obtained when the cavity is not inclined and for the case with a pseudo-plastic working fluid (n < 1).…”
Section: Introductionmentioning
confidence: 99%
“…To approximate and solve the described system of nonstationary differential equations ( 1)-( 5), various schemes based on the finite difference procedure have been used (Loenko et al, 2021a(Loenko et al, , 2021b. The method of successive over relaxation has been applied to solve the approximated Poisson equation ( 1).…”
Section: Methods Of Solution and Validationmentioning
confidence: 99%
“…Their analysis revealed that enhancing thermal radiation upsurges the energy profile adjacent to the stretching sheet. However, the detailed study on flow and thermal behavior of non-Newtonian fluids is in References [5,6,[28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in non‐Newtonian fluids, viscosity varies with their strain rate, owing to this reason these fluids do not have fixed or constant viscosity. Grease, cheese, lava, liquid soaps, paints, cosmetics, petroleum, mayonnaise, saliva, blood, jam, soup, butter, toothpastes, magma, synovial fluid, and many others are examples of non‐Newtonian fluids 4–6 . However, Walters‐B fluid, Powell–Eyring fluid, Casson fluid, Jeffrey fluid, Maxwell fluid, Williamson fluid, and micropolar fluids are very important non‐Newtonian fluids due to their significant industrial applications.…”
Section: Introductionmentioning
confidence: 99%